Rheological characterisation of full-fat and reduced-fat aerated icings - Meza, Barbara Erica del Valle (2021)
Aerated icings are a sweet, fat-rich, and uncooked type of glaze material made by whipping sugar and fat together to form a bubbly fluid. The rheological behaviour of full-fat and reduced-fat aerated icings was characterised using rotational rheometry techniques. Control full-fat formulations were prepared using commercial icing sugar and unsalted butter (a viscoplastic fat-based continuous phase) in a 2:1 ratio. Reduced-fat samples were prepared by replacing 25% and 50% of butter by mass by a 50% w/w of native corn starch suspension (a potential carbohydrate-derived fat replacer). Icings with different air volume fractions were prepared by mixing in a planetary mixer for 3 min or 6 min (air volume fractions ≤ 0.17). The size distribution of sugar crystals and air bubbles were similar, with modal values near 10 μm. The experimental data from flow curves and creep tests were described well by the Bingham and Burgers models, respectively. Flow behaviour and static yield stress values were affected by the mixing time and the butter replacement, whereas the viscoelastic behaviour was only influenced by the latter. The information obtained in this study can be used to assess whether these reduced-fat products are suitable for the flow and coating stages of manufacturing.